Simulation of 20.96% Efficiency n-type Czochralski UMG Silicon Solar Cell. (August 2016) - Zheng, Peiting; Rougieux, Fiacre E.; Samundsett, Chris; Yang, Xinbo; Wan, Yimao; Degoulange, Julien; Einhaus, Roland; Rivat, Pascal; Macdonald, Daniel
Abstract: In this paper, we present the 3D simulation of>20% efficiency solar cells using n- type 100% Upgraded-Metallurgical Grade (UMG) Czochralski (CZ) silicon and Electronic Grade (EG) Float Zone (FZ) fabricated using the same process. The cells have a passivated emitter rear locally diffused (PERL) structure, with an etch-back approach on the rear to maintain high bulk lifetime in the cells via phosphorus gettering. Simulation ofthe power losses of both devices are analysed as a function of measured material and cell parameters, including minority carrier lifetime, reflectance, contact resistivity and recombination parameters of the diffused and non-diffused surfaces.